Comportamiento agronómico del cultivo de lechuga (Lactuca sativa L.). Con diferentes abonos orgánicos, en el colegio pueblo nuevo cantón El Empalme, año 2014 - Terán Burgos, Dionicio Ricardo (2015)
The present investigation was established in the Agricultural Technical College "Pueblo Nuevo", belonging to the parish The Guayas, Canton El Empalme. The research lasted 60 days, using a Design Randomized Complete Block (DBCA), with seven treatments and four replications. To determine the average resorted to the use of multiple range test Tukey 95% probability. From the results of research conducted to introduce better treatment throughout obtained sheet was T6 (Dunger 5 kg) values of 20.75 cm and 14.50 cm, respectively, while the greater height of leaves was obtained with the T2 (Humus 3 kg) with a value of 22.50 cm. The T5 (Dunger 3 kg) treatment was the treatment had higher stem diameter with a value of 1.93 cm, with data from 212,50 gr total weight best demonstrated in T5 (Dunger 3 kg) and T6 ( Dunger 5 kg) .The higher mortality percentage of the crop plants were observed in the T2 (Humus 3 kg) with values of 8.75 plants, while the best dessmotro weight per plot at T4 (Dunger 1 kg) with a value of 2200.00 gr, at the end of harvest. The treatment presented a better cost / benefit ratio was T6 (5 kg Dunger) was the treatment that higher economic rate where it is determined that for every dollar invested will have a profit of $ 2.73 cents.